A Melanin‐Based Natural Antioxidant Defense Nanosystem for Theranostic Application in Acute Kidney Injury. (25th September 2019) - Sun, Tuanwei; Jiang, Dawei; Rosenkrans, Zachary T.; Ehlerding, Emily B.; Ni, Dalong; Qi, Chao; Kutyreff, Christopher J.; Barnhart, Todd E.; Engle, Jonathan W.; Huang, Peng; Cai, Weibo
Abstract: Acute kidney injury (AKI) is frequently associated with oxidative stress and causes high mortality annually in clinics. Nanotechnology‐mediated antioxidative therapy is emerging as a novel strategy for the treatment of AKI. Herein, a novel biomedical use of the endogenous biopolymer melanin as a theranostic natural antioxidant defense nanoplatform for AKI is reported. In this study, ultrasmall Mn 2+ ‐chelated melanin (MMP) nanoparticles are easily prepared via a simple coordination and self‐assembly strategy, and further incorporated with polyethylene glycol (MMPP). In vitro experiments reveal the ability of MMPP nanoparticles to scavenge multiple toxic reactive oxygen species (ROS) and suppress ROS‐induced oxidative stress. Additionally, in vivo results from a murine AKI model demonstrate preferential renal uptake of MMPP nanoparticles and a subsequent robust antioxidative response with negligible side effects according to positron emission tomography/magnetic resonance (PET/MR) bimodal imaging and treatment assessment. These results indicate that the effectiveness of MMPP nanoparticles for treating AKI suggests the potential efficacy of melanin as a natural theranostic antioxidant nanoplatform for AKI, as well as other ROS‐related diseases. Abstract : Mn 2+ ‐chelated melanin (MMPP) nanoparticles with ultra‐small hydrodynamic size are facilely prepared via a simple coordination and self‐assembly strategy, and further PEGylation. MMPP nanoparticles exhibit excellent in vivo circulation and preferential renal uptake in a murine acute kidney injury (AKI) model. Importantly, MMPP nanoparticles can act as efficient reactive oxygen species scavengers to alleviate AKI via antioxidative protection.